Perancangan dan Implementasi Video Company Profile Jurusan Perhotelan di SMK Satu Bangsa Harmoni - Eryc Eryc; Dean Mervyn (National Conference for Community Service Project (NaCosPro), 2023)
SMK Satu Bangsa Harmoni School is a private school located in Benkong Jaya No.1 Top 100 Batam, Bengkong Laut, in Bengkong District. The SMK Satu Bangsa Harmoni School was officially established on June 27, 1997 and has been operating since March 3, 2008. Due to the lack of information about the school, many people are not familiar with the SMK Satu Bangsa Harmoni School, especially in Batam. Therefore, the author will design a video profile for the hospitality accommodation major at SMK Satu Bangsa Harmoni Batam. The design starts with taking material in the form of a video at the partner directly with the Redmi Note 4 camera. After taking the material, the author will edit the video with the Adobe Premiere Pro 2020 software. After the video has been edited, the video results are given to the SMK Satu Bangsa Harmoni Batam school to upload to the school's social media as a promotion.